Miradas políticas de la elite en una zona decadente. El norte chico entre 1880 y 1900 - Rubio Apiolaza, Pablo (Revista de Historia Social y de las Mentalidades, 2011)
Since the 1880’s decade, the districts of Atacama a nd Coquimbo went through a great social and economic depression, mainly because of t he crisis in their most important exporting activity, mining. This had it’s counterpa rt in Chilean politics, the real importance of these provinces was seriously diminished, in com parison to the active role that they had in the middle of that century. This study, analyses , through a specific moment in time, the most important aspects of the “decadence of politic s”, emphasizing on the 1890 national strike, the 1891 civil war, the social violence and the requests for public policies to end the crisis of these regions.